Regulation of Bacteroides acidifaciens by the aryl hydrocarbon receptor in IL-22-producing immune cells has sex-dependent consequential impact on colitis - Mitchell, Chandani; Staley, Shanieka; Williams, Michal Claire; Saxena, Archana; Bogdon, Raymond; Roark, Kasie; Hailey, Michele; Miranda, Kathryn; Becker, William; Dopkins, Nicholas; Pena, Maria Marjorette; Hogan, Kristen M.; et al. (Frontiers in Immunology, 2024)
Introduction Colitis is an inflammatory bowel disease (IBD) characterized by immune cell dysregulation and alterations in the gut microbiome. In our previous report, we showed a natural product in cruciferous vegetables and ligand of the aryl hydrocarbon receptor (AhR), indole-3-carbinol (I3C), was able to reduce colitis-induced disease severity and microbial dysbiosis in an interleukin-22 (IL-22) dependent manner. Methods In the current study, we performed single-cell RNA sequencing (scRNAseq) from colonocytes during colitis induction and supplementation with I3C and show how this treatment alters expression of genes involved in IL-22 signaling. To further define the role of IL-22 signaling in I3C-mediated protection during colitis and disease-associated microbial dysbiosis, we generated mice with AhR deficiency in RAR-related orphan receptor c (Rorc)-expressing cells (AhRΔRorc) which depletes this receptor in immune cells involved in production of IL-22. Colitis was induced in wildtype (WT), AhRΔRorc, and littermate (LM) mice with or without I3C treatment. Results Results showed AhRΔRorc mice lost the efficacy effects of I3C treatment which correlated with a loss of ability to increase IL-22 by innate lymphoid type 3 (ILC3s), not T helper 22 (Th22) cells. 16S rRNA microbiome profiling studies showed AhRΔRorc mice were unable to regulate disease-associated increases in Bacteroides, which differed between males and females. Lastly, inoculation with a specific disease-associated Bacteroides species, Bacteroides acidifaciens (B. acidifaciens), was shown to exacerbate colitis in females, but not males. Discussion Collectively, this report highlights the cell and sex-specific role of AhR in regulating microbes that can impact colitis disease.